Urbanization and caregiving: a framework for analysis and examples from southern and eastern Africa - Engle, Patrice L.; Menon, Purnima; Garrett, James L.; Slack, Alison T. (SAGE Publications, 1997)
This paper considers the role of caregiving on children's health and development with a special focus on identifying the constraints on effective caregiving in urban areas, and the potential solutions. It uses the extended UNICEF framework for nutrition which suggests that there are six major types of care behaviour: feeding and breast-feeding, food preparation and handling, hygiene behaviour, psycho-social care, care for women and home health practices. To ensure adequate care for the child, the caregiver needs adequate knowledge and education, physical and mental health, autonomy in decision-making, time, and social support from the family and community. This paper describes each of these resources and constraints, and two of the behaviour types (breast-feeding and health care utilization) in the urban areas of eight countries in eastern and southern Africa. It also presents a matrix highlighting critical constraints on caregiving behaviours in urban areas, and potential solutions, and identifies areas where further research is needed.